Design and application of stimuli-responsive DNA hydrogels: A review. (December 2022) - Wang, Zhiguang; Chen, Ruipeng; Yang, Shiping; Li, Shuang; Gao, Zhixian
Abstract: Deoxyribonucleic acid (DNA) hydrogels combine the properties of DNAs and hydrogels, and adding functionalized DNAs is key to the wide application of DNA hydrogels. In stimuli-responsive DNA hydrogels, the DNA transcends its application in genetics and bridges the gap between different fields. Specifically, the DNA acts as both an information carrier and a bridge in constructing DNA hydrogels. The programmability and biocompatibility of DNA hydrogel make it change macroscopically in response to a variety of stimuli. In order to meet the needs of different scenarios, DNA hydrogels were also designed into microcapsules, beads, membranes, microneedle patches, and other forms. In this study, the stimuli were classified into single biological and non-biological stimuli and composite stimuli. Stimuli-responsive DNA hydrogels from the past five years were summarized, including but not limited to their design and application, in particular logic gate pathways and signal amplification mechanisms. Stimuli-responsive DNA hydrogels have been applied to fields such as sensing, nanorobots, information carriers, controlled drug release, and disease treatment. Different potential applications and the developmental pro-spects of stimuli-responsive DNA hydrogels were discussed. Graphical abstract: Image 1 Highlights: DNA hydrogel, favored by researchers, combines properties of DNA and hydrogels. Both DNA and skeleton, having many response characteristics, can respond to stimuli. Sensing, nano robots, information carriers, drug delivery, and disease treatment uses. Three stimulus response types: single biological, single abiotic and compound.